The Role of Dynamic Capability in Mediating the Effects of Environmental Dynamism and Managerial Capabilities on Firm Performance: a Preliminary Study - Adrian Permana; Lena Ellitan (Program MM Universitas Surabaya, 2020)
SSmall and Medium Enterprises (SMEs) face many challenges from the coming rapid changes such as technology advancement, competitions, limitations and supports from government regulations, and limitations in terms of capital supply, product knowledge, and company management. Building and maintaining the firm performance of SMEs can be achieved through external factors (environmental dynamism) and internal factors (managerial capabilities). By using the dynamic capabilities as an intervening variable, it is expected to have an impact on firm performance by measuring the perceptive from owners or managers of SMEs. By using PLS-SEM analysis, the selected samples in this study consisted of 30 owners or managers of SMEs from Surabaya, Indonesia. The results indicated that the environmental dynamism and managerial capabilities have a significant influence on firm performance with dynamic capabilities as the intervening variables. Environmental dynamism also has a significant influence on firm performance. Meanwhile, managerial capabilities do not have a significant influence on firm performance.